Health literacy, myths and stigma among patients with Parkinson’s disease in the Republic of Moldova - ROTARU, Lilia; GROSU, Oxana; CEBUC, Mădălina; CARAUSU, Ghenadie; VOVC, Victor; GROPPA, Stanislav (One Health & Risk Management, 2025)
Introduction: Health literacy, defined as an individual’s ability to make health-related decisions based on acquired knowledge, impacts the quality of life of patients with Parkinson’s disease (PD). This study aims to establish a baseline assessment of health literacy, common myths, and stigma among PD patients in the Republic of Moldova. Material and Methods: This cross-sectional study was conducted at the ”Diomid Gherman” Institute of Neurology and Neurosurgery (2022 -2023). Descriptive and inferential statistics were applied (the chi-square test; 95 % CI). A total of 103 PD patients (52.4% women, 47.6% men; mean age 65.5 years) participated and completed the Knowledge, Attitude, and Practices questionnaire. Results: Most PD patients attributed the disease to stress (61.2%), impaired brain blood flow (49.5%), poor brain oxygenation (44.7%), and exposure to toxic substances (13.6%), particularly among those with lower education (p=0.001). Tremors are associated with PD in 30.1% of cases, while 21.4% believe PD shortens life expectancy. Concerns on treatment include 15.5% of patients who believe medication as being "toxic" and 6.8% that L-dopa accelerates disease progression. Self-stigma includes feelings of shame (46.6%), fear of judgment (44.7%), social isolation (32.0%), and reduced independence (65%). Conclusions: The study has revealed limited health literacy and significant self-stigma among PD patients in Moldova, highlighting misconceptions and social impacts of the disease, especially in less educated individuals. Enhancing health literacy and reducing stigma are crucial for improving patient care.